2022
DOI: 10.1038/s41563-022-01323-0
|View full text |Cite
|
Sign up to set email alerts
|

Cell clusters softening triggers collective cell migration in vivo

Abstract: Embryogenesis, tissue repair and cancer metastasis rely on collective cell migration. In vitro studies propose that cells are stiffer while migrating in stiff substrates, but softer when plated in compliant surfaces which are typically considered as non-permissive for migration. Here we show that cells within clusters from embryonic tissue dynamically decrease their stiffness in response to the temporal stiffening of their native substrate to initiate collective cell migration. Molecular and mechanical perturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 59 publications
3
23
0
Order By: Relevance
“…( 2018 )). Interestingly, recent studies found that PIEZO1 inhibition suppresses collective migration and results in a decrease in the directionality of migrating Xenopus neural crest cells ( Canales Coutiño and Mayor ( 2021 ); Marchant et al . ( 2022 )).…”
Section: Discussionmentioning
confidence: 99%
“…( 2018 )). Interestingly, recent studies found that PIEZO1 inhibition suppresses collective migration and results in a decrease in the directionality of migrating Xenopus neural crest cells ( Canales Coutiño and Mayor ( 2021 ); Marchant et al . ( 2022 )).…”
Section: Discussionmentioning
confidence: 99%
“…Though the feasibility of altering the morphology and focal adhesion of individual cell through programming the reconfigurations of scaffold micro-structures has been widely investigated and the potential outcomes of evoking the cascade of gene expression via mechanotransduction could be predicted, it is still difficult to assume the similar effects on the collective behaviours and functions of the amounts of cells involving complicated cell-cell interactions. 120,121 By using SMPs and micro-fabrication/micro-embossing methods, a variety of scaffolds with temperature-actuated reconfigurable microstructures, enabling reconfigurations either from micro-/nano-topographies to flat or in a reverse way, have been developed and employed to investigate the mechanotransduction of dynamic topographical cues on collective cellular behaviours and functions. 28,[122][123][124][125] For different cell models such as NIH-3T3 fibroblast cell lines, 28,122 primary mouse embryonic fibroblasts, 122 and human-derived stem cells, 123,124 the reconfigurations of scaffold micro-structures could always cause the switches of cellular shapes and reorientations of cytoskeletons for a large number of cells.…”
Section: Adaptive Tissue Regeneration Assisted By Scaffolds With Reco...mentioning
confidence: 99%
“…As described above, an increase in mesoderm stiffness is required to induce NC EMT and migration ( Barriga et al, 2018 ). However, recent work has shown that pre-migratory NC cells respond to the increased substrate stiffness by changing their mechanical properties ( Marchant et al, 2022 ). In this mechanism, NC cells activate the mechanosensitive Piezo1 channel, causing NC cells to reduce microtubule (MT) acetylation ( Figure 2H ).…”
Section: The Physical Responses Of Migrating Cells To Their Surroundingsmentioning
confidence: 99%